here's the solution,
let the length of shorter peice = x
then the lenght of longer peice = 6x + 8
now, we know that the sum of length of peices measures 99 feet,
So,
=》x + 6x + 8 = 99
=》7x = 91
=》x = 13
shorter piece length = 13 feet
longer peice length = 13 × 6 + 8 = 78 + 8 = 86 feet
Answer:
48
Step-by-step explanation:
x=48
Answer:
I resolve the expression
(4x+3) (3x-8)=12x2-32x+9x-24
12x2-23x-24
the polynomial (4x+3) (3x-8) is equivalent a the expression 12x2-23x-24
Answer:
A. As the value of x increases, the value of f(x) moves toward a constant
Step-by-step explanation:
An exponential function with a base less than 1 will decay to zero. Here, the exponential has -2 added to it, so the decay is toward the value -2.
An exponential function is defined for all real numbers. This one has a y-intercept of -1.
C. y= x + 4
If you plug it in
1 + 4=5
6 + 4 = 10
8 + 4 = 12
and so forth